Transformasi Kemampuan Problem Solving Mahasiswa dengan Model Experiential Learning berbasis Digital Litercy pada Pembelajaran Kewirausahaan - Elvi Rahmi; Friyatmi (Jurnal Ecogen, 2025)
This study objectives to apply the Digital Literacy-based Experiential Learning Model (EL-DL) in an effort to transform students' problem-solving skills. The research  used an experimental method with a pretest-posttest control group design. The experimental class consisted of 32 students who received experiential learning-based treatment with the integration of digital literacy, while the control class consisted of 30 students who received conventional entrepreneurship learning. The research instrument was a problem-solving ability test administered before (pretest) and after (posttest) the treatment in both groups. Before use, the test instruments underwent validity, reliability, difficulty level, and discrimination tests to ensure the quality of the questions. The data obtained was analyzed by calculating the gain score to determine the increase in students' problem-solving skills, followed by a t-test to compare the learning outcomes between the experimental class and the control class. The results of this study indicate that the application of the Digital Literacy-based Experiential Learning Model (EL-DL) has a significant positive impact on students' problem-solving skills compared to conventional methods.  Based on these findings, universities are advised to integrate EL-DL more systematically. Students also need to be encouraged to improve their digital literacy so that they can be more independent in searching for, evaluating, and processing information as a means of strengthening their problem-solving skills